Mousemobile - Breitrose, Prudence E. (Breitrose, Prudence E. Mousenet book., 2013)
"Eleven-year-old Megan and her cousin Joey have a summer job working with computer-savvy mice to spread the word about climate change. But when there's trouble at Headquarters, Megan and Joey find themselves on a cross-country journey to save Mouse Nation, and the planet, from a mysterious enemy"--